2022
DOI: 10.3389/fmed.2022.867293
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Epidemiological Characteristics of Patients With Inflammatory Bowel Disease in Egypt: A Nationwide Multicenter Study

Abstract: Background and AimsUlcerative colitis (UC) and Crohn's disease (CD) are the most common types of Inflammatory bowel disease (IBD), with variable responses to traditional therapies and unpredicted prognosis. In Egypt and most developing countries, the lack of recent epidemiological and prognostic data adversely affects management strategies. We collected and analyzed data of patients with IBD from multiple centers across Egypt to evaluate patients' clinical and epidemiological characteristics.MethodsThis retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…As regard disease extent, 78.3% of the IBD patients were left sided colitis. This agrees with the study which reported that the predominance of left sided colitis in 75.6% of the UC group (12) . Intestinal Fatty Acid Binding Protein (I-FABP) is considered one of the factors associated with etiopathogenesis of IBD as it can be released into the circulation as soon as the cell membrane integrity is compromised (14) .…”
Section: Discussionsupporting
confidence: 93%
“…As regard disease extent, 78.3% of the IBD patients were left sided colitis. This agrees with the study which reported that the predominance of left sided colitis in 75.6% of the UC group (12) . Intestinal Fatty Acid Binding Protein (I-FABP) is considered one of the factors associated with etiopathogenesis of IBD as it can be released into the circulation as soon as the cell membrane integrity is compromised (14) .…”
Section: Discussionsupporting
confidence: 93%
“…They concluded that apart from bleeding and diarrhea colonoscopic examination is unlikely to discover serious colonic disease in patients with GIT symptoms. These results support ours, as diarrhea was the main symptom (80%) of our IBD patients with nearby prevalence previously reported [22,23]. Also, 70% of our IBS patients were presented with abdominal pain and similar prevalence was previously reported [24,25].…”
Section: Discussionsupporting
confidence: 93%
“…In Egypt, the incidence of ulcerative colitis has grown during the past ten years (Lynch and Hsu, 2022). Patients with UC displayed a higher prevalence (59.2%) in Egypt and further, 70.5% were from North of Egypt (Elbadry et al, 2022). Previous studies of health maintenance programs were conducted on ulcerative colitis for reducing signs and symptoms through medication adherence without focusing on life style modification so, staying up-todate with life-long health care maintenance of patients with ulcerative colitis is critical especially in remission phase.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…An early and accurate diagnosis, thorough evaluation of the patient's risk factors for negative outcomes, and then the commencement of effective, safe, and tolerable drugs is all necessary for the management of UC. Reaching a sustained steroid-free remission with appropriate normal health-related quality of life (QoL), preventing morbidity, such as frequent hospitalization and colectomy, and preventing colon cancer are the ideal therapeutic goals (Eltaweel and Elbadry, 2021). Inducing and keeping remission from UC is the major goal of treatment, with the long-term objectives of avoiding disability, colectomy, and colon cancer as secondary objectives.…”
Section: Introductionmentioning
confidence: 99%